Dabigatran affects thrombin-dependent platelet aggregation after a week-long therapy. (4th July 2018) - Sokol, Juraj; Nehaj, Frantisek; Ivankova, Jela; Mokan, Michal; Mokan, Marian; Stasko, Jan
Abstract: Objective. Dabigatran is a direct thrombin inhibitor. As the main adverse event is bleeding, it is relevant whether dabigatran has additional effects on platelet function. If so, it could affect the bleeding risk. We aimed to assess in vitro aggregation in patients with atrial fibrillation (AF) receiving dabigatran. Design. We evaluated 32 AF patients treated with dabigatran (study group) and 18 non-anticoagulated non-AF blood donors (control group). We assessed light transmittance platelet aggregation (LTA) with 100 nmol/L γ-thrombin in both groups. The LTA was performed at two time-points in our dabigatran group of patients. Results. The thrombin-induced platelet aggregation was significantly lower two hours after dabigatran was taken compared to baseline measurement (9% ± 6% vs. 29% ± 21%) in our study group. Moreover, we observed that the baseline value of platelet aggregation in patients on dabigatran treatment was significantly lower compared to healthy volunteers (29% ± 21% vs. 89 ± 8). However, one subanalysis showed that this significant reduction in platelet aggregation at baseline was only observed in patients who received dabigatran for over a week. Conclusion. The thrombin-induced platelet aggregation is reduced in non-valvular AF patients receiving dabigatran after a week-long therapy.